Construction of nano-SiOx encapsulated in two-dimensional nitrogen and phosphorous co-doped nanosheets for Li-ion batteries - Zhang, Qingfen; Tan, Hongjin; Lin, Fenglong; Hsu, Wayne; Wang, Shenglong; Wu, Yincai; Wang, Huihui; Li, Bangmin; Song, Lijun (New journal of chemistry, 2025)
Silicon suboxide (SiOx) has been the subject of considerable research interest owing to its promising theoretical specific capacity and lower volume expansion compared with nano-silicon. However, improving its rate and cycling performance is crucial for practical applications. In this study, we propose a novel composite anode material of nano-SiOx encapsulated in a two-dimensional (2D) nitrogen and phosphorous (N/P) co-doped graphene-like nanosheet structure. In half-cell tests, the electrode with this active material exhibited a reversible capacity of 543.0 mA h g−1 at 400 mA g−1 after 100 cycles and 386.4 mA h g−1 at 1600 mA g−1, an improvement of two orders of magnitude compared with pristine micron-SiOx. A thorough study revealed that this excellent battery rate performance and capacity retention primarily resulted from the role played by the N/P co-doped 2D graphene-like framework, which not only effectively promoted the kinetics of ionic and electronic migration but also likely reduced the interfacial parasitic reactions in the electrolyte and mitigated volume expansion by forming a “caged” framework over nano-SiOx. Thus, this work demonstrates a simple and feasible method for the preparation of high-performance anode materials, offering a promising strategy to address the challenges of volume expansion and sluggish kinetics in SiOx-based anodes for lithium-ion batteries.